Aldehyde-Appended Distyrylbenzenes: Amine Recognition in Water - Kumpf, Jan; Bunz, Uwe H. F. (Chemistry : a European journal, 2012)
Change in water: Aqueous solutions of aldehyde-substituted, water-soluble distyrylbenzenes reacted with amines to give imines or aminals with dramatically changed fluorescence. This approach allowed the detection and recognition of amines in water (see figure).